Work developed in the area of patients with special needs: a bibliometric analysis of the annals of the Brazilian Dental Research Society (SBPqO) - Gabriela Mancia de Gutierrez; Carlos Felipe Bonacina; Vanessa Lira Siqueira; Ana Cristina Fernandes Maria Ferreira; Maria Teresa Botti Rodrigues Santos (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2023)
Aim: To carry out a bibliometric analysis of the papers presented at the Meetings of the Brazilian Society for Dental Research (SBPqO) about Dentistry for Patients with Special Needs (DPSN). Materials and Methods: The annals published from 2013 to 2022 were accessed and the following search terms were used for data collection: "disabled", "special needs", "syndrome", "special patient", "special patients" and "people with disabilities" in all annals. The data were submitted to descriptive analysis, with the absolute and relative frequency of the analyzed variables being exposed. Results: 558 abstracts were found, 230 were excluded because they did not fit the DPSN theme, ending with 328 abstracts. Most studies were observational (n=287; 87.5%), 2019 was the year with the highest number of publications (n=51; 15.5%). The Southeast was the region with the highest number of published abstracts (n=204; 62.2%) followed by the Northeast (n=54; 16.5%), public institutions had a significant participation with more than two thirds (n= 236; 72%). Discussion: The number of jobs in the DPSN area had been growing over the years, there was a drop in production during the pandemic, but this number is growing again. Conclusion: Despite all the public policies to include care for disabled people in dental care and twenty years after the specialty became official in Brazil, we still do not have this category as an area in the SBPqO that is so necessary for the development of scientific knowledge in the area.